Biohydrogen from organic wastes as a clean and environment-friendly energy source: Production pathways, feedstock types, and future prospects. (December 2021) - Saravanan, A.; Senthil Kumar, P.; Khoo, Kuan Shiong; Show, Pau-Loke; Femina Carolin, C.; Fetcia Jackulin, C.; Jeevanantham, S.; Karishma, S.; Show, Kuan-Yeow; Lee, Duu-Jong; Chang, Jo-Shu
Highlights: Agricultural residue is an alternative source for biohydrogen production. Various fermentation processes for biohydrogen production are evaluated. The incorporation of nanotechnology with enzymes enhances the biohydrogen production. Alternative approaches and mechanism studies for hydrogen production are reviewed. Application and future challenges of biohydrogen production are discussed in depth. Abstract: Microbial fermentation of organic matter under anaerobic conditions is currently the prominent pathway for biohydrogen production. Organic matter present in waste residues is regarded as an economic feedstock for biohydrogen production by dark and photo fermentative bacteria. Agricultural residues, fruit wastes, vegetable wastes, industrial wastewaters, and other livestock residues are some of the organic wastes most commonly used for biohydrogen production due to their higher organic content and biodegradability. Appropriate pretreatments are required to enhance the performance of biohydrogen from complex organic wastes. Biohydrogen production could also be enhanced by optimizing operation conditions and the addition of essential nutrients and nanoparticles. This review describes the pathways of biohydrogen production, discusses the effect of organic waste sources used and microbes involved on biohydrogen production, along with addressing the key parameters, advantages, and difficulties in each biohydrogen production pathway.